Enhancing geospatial tools through integration of climate data: A path toward more sustainable infrastructure planning and decision-making - Rostén, Mia; Lönkvist, Vendela (My University, 2025)
Climate impact is an important dimension in today’s urban planning since the construction of new roads contributes to large emissions of greenhouse gases as well as environmental impacts on the ecosystem. One approach, part of the strategies from the action plan developed by governmental initiative Fossilfritt Sverige, to mitigate climate impact relates to increased use of digital tools of which includes different types of geo tools. The objective of this thesis is to investigate if climate data can be effectively integrated into a Geo tool and to evaluate its role in mitigating climate impacts in infrastructure projects. Furthermore, to analyze to what extent geo tools can support and streamline decision-making during the early design phase in infrastructure projects. This study examines a route analysis planning tool named Georaptor using a weighting method called AHP. To determine whether the weighting method is effective in drawing conclusions based on climate data, a case study was conducted in the area around Bergkvara, Kalmar County. In addition, perspectives from previous projects, expert opinions, and comparisons between different weightings were analyzed. The result reveals that the tool is useful for analyzing where to construct a road in a given area, taking climate impacts into account. By identifying areas with high ecological value, it is possible to avoid sensitive areas and thereby reduce the road’s carbon footprint and preserve important natural values. The tool helps streamline the decision-making process by quickly generating multiple corridor alternatives during the design phase, which can later be manually evaluated. This minimizes the workload and provides transparency, as both good and less favorable alternatives are compared.
Keywords: Digitalization, Geo tool, Sustainability, Environmental Engineering, Georaptor, Infrastructure planning, Climate data.